A recombinant avian adeno-associated virus as a vector for infectious bursal disease vaccination. - Perozo, Francisco; Villegas, Pedro; Estévez, Carlos; Alvarado, Ivan; Purvis, Linda (Revista Científica de la Facultad de Ciencias Veterinarias, 1970)
Infectious bursal disease is a worldwide distributed immunosuppressive disease of young chickens that need to be controlled by vaccination; it represents one of the main concerns for the poultry industry. The adeno-associated viruses are non-pathogenic viruses, capable of accommodating relatively long pieces of DNA, and of infecting a wide variety of cell types. A member of this family, the avian adeno-associated virus has been fully characterized and successfully used for gene delivery in chicken embryo tissues and cells. In this study, it was demonstrated by electron microscopy and immunocitochemistry the feasibility of generating recombinant avian adeno-associated virus (rAAAV) virions expressing the immunogenic viral protein 2 of infectious bursal disease virus (IBDV). Serological evidence of VP2 protein expression measured as IBDV specific antibody response after in ovo or intramuscular inoculation of the recombinant virus in specific pathogen free (SPF) chickens was observed. The use of rAAAV virions for gene delivery in poultry is a promising approach to poultry vaccination.